(3GdeOjQ GdeYGUQ (B:s (3EOGQI GdCYeGd aj HjFI GdYhdeI GdeYGUQI (B/s - (3CHh HcQ, eUWaj eMehOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2003)
(3GdEOGQI GdaYGdI MJejI dehGLI GdJMOjGJ aj HjFI GdCYeGd GdeYGUQI(B-(3GdJNWjW(B-(3GdeOjQ GdeYGUQ hGdJNWjW(B-(3GdJfXje GdEOGQj aj GdefXeGJ GdeYGUQI(B-(3JUeje Gdgjcd GdJfXjej hEYOGO GdENJUGUGJ GdJfXjejI(B-(3GdgjGcd GdhXjajI hHWGbGJ hUa GdhXGFa(B-(3GdeOjQ GdeYGUQ hcaGAI CYeGd GdeJGHYI hGdQbGHI hJbjje GdCOGA(B-(3GdebheGJ GdQFjSjI dcaGAI GdeOjQ GdeYGUQ(B-(3KbGaI GdefXeGJ GdMchejI hJCKjQgG Ydi NUGFU GdLgGRs
Keywords: (3EOGQI GdCYeGds; (3GdJNWjWs; (3GdYhdeIs